• Предмет: Математика
  • Автор: lizawin2010
  • Вопрос задан 4 года назад

0,8×(600×0,01+0,07×100)-0,04×(7000×0,1+0,4×100)​

Ответы

Ответ дал: Zombynella
0

Ответ:

В решении.

Пошаговое объяснение:

Вычислить:

0,8×(600×0,01+0,07×100)-0,04×(7000×0,1+0,4×100)​;

0,8(600*0,01+0,07*100)-0,04(7000*0,1+0,4*100) =

= 0,8(6 + 7) - 0,04(700 + 40) =

= 0,8 * 13 - 0,04 * 740 =

= 10,4 - 29,6 = -19,2.

Ответ дал: fahmadzada07
0

Ответ:

Ответ-33,6

!!!!!!!!!!!!

Приложения:

Zombynella: Во второй строке в конце ошибка, не 400, а 40. Поправьте.
fahmadzada07: Понятно
fahmadzada07: Ошиблась
Похожие вопросы